2019
DOI: 10.3390/ijms20051061
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of the TP53-Induced Glycolysis and Apoptosis Regulator (TIGAR) Sensitizes Glioma Cells to Hypoxia, Irradiation and Temozolomide

Abstract: The TP53-induced glycolysis and apoptosis regulator (TIGAR) has been shown to decrease glycolysis, to activate the pentose phosphate pathway, and to provide protection against oxidative damage. Hypoxic regions are considered characteristic of glioblastoma and linked with resistance to current treatment strategies. Here, we established that LNT-229 glioma cell lines stably expressed shRNA constructs targeting TIGAR, and exposed them to hypoxia, irradiation and temozolomide. The disruption of TIGAR enhanced leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…The enhancement of glycolysis is a principal characteristic of energy metabolism during glioma development in hypoxic conditions [10]. It has been demonstrated that HIF-1α activation in response to hypoxic stimuli can constitutively promote the expression of glycolytic genes, such as LDHA, GLUT1, HK2 and PKM2, in GBM cells to regulate tumor glycolysis [11,44]. Here, we demonstrated that RLIP76 drives a positive feedback loop to promote the HIF-1α-related signaling pathway by stabilizing HIF-1α, leading to the promotion of hypoxia-induced glycolysis in hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The enhancement of glycolysis is a principal characteristic of energy metabolism during glioma development in hypoxic conditions [10]. It has been demonstrated that HIF-1α activation in response to hypoxic stimuli can constitutively promote the expression of glycolytic genes, such as LDHA, GLUT1, HK2 and PKM2, in GBM cells to regulate tumor glycolysis [11,44]. Here, we demonstrated that RLIP76 drives a positive feedback loop to promote the HIF-1α-related signaling pathway by stabilizing HIF-1α, leading to the promotion of hypoxia-induced glycolysis in hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…157 It has also been recognized that HIF-1α transformed glycolysis to pentose phosphate pathway. 158 Mechanically, HIF-1α induced glucose uptake and lactate accumulation, lowered intracellular ATP concentrations, and elevated mitochondrial membrane potential, which was paralleled with the expression level GLUTs, HKⅡ, PKM2, PDK1, and LDH-A. 29 Interestingly, HIF-1α overexpression facilitated the VEGF pathway of vasculogenesis.…”
Section: Interplay Of Transcription Factors In Aerobic Glycolysis Hif-1αmentioning
confidence: 97%
“…34,62 Moreover, growth inhibition was also associated with tumor vessels reduction, enhanced levels of ROS, and autophagic responses. 64,158,159 HIF-1α signaling was also involved in regulating the metabolism, tumor-specific immunity, and tumor growth in glioma. 160 Regarding the effects of chemotherapy and radiotherapy, HIF-1α signaling participated in regulating effectiveness of irradiation and temozolomide of glioma via the glycolytic process.…”
Section: Interplay Of Transcription Factors In Aerobic Glycolysis Hif-1αmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has reported that the high expression level of PDK1 played an obligate role in the resistance of cisplatin chemotherapy for ovarian cancer [30]. Maurer et al reported that the TP53-induced glycolysis and apoptosis regulator (TIGAR) regulated glycolysis and induced chemoresistance of glioblastoma to temozolomide, which was mediated by HIF-1α [31]. In tumor, cancer cells coexist with multiple non-neoplastic stromal cells, together creating the tumor microenvironment.…”
Section: Glucose and Energy Metabolismmentioning
confidence: 99%